Accuracy of intentionally tilted implant placement in the maxilla using dynamic navigation: a retrospective clinical analysis. Issue 4 (April 2022) - Meng, T.; Zhang, X.
Abstract: The aim of this retrospective study was to investigate the accuracy of dynamic navigation for the placement of intentionally tilted implants in the posterior maxilla. The study included 12 patients with edentulism or continuous multiple tooth loss, who had 48 implants inserted under dynamic navigation guidance in the posterior maxilla. Twenty-four implants near maxillary sinuses were intentionally tilted. The average platform deviation was 1.3 ± 0.4 mm (range 0.8–2.3 mm), apex deviation was 1.1 ± 0.5 mm (range 0.2–2.3 mm), and axis deviation was 3.1 ± 1.0° (range 1.8–6.7°). The other 24 implants were axially positioned. The average platform deviation was 1.5 ± 0.5 mm (range 0.7–3.1 mm), apex deviation was 1.3 ± 0.7 mm (range 0.5–3.1 mm), and axis deviation was 3.2 ± 1.5° (range 1.5–7.7°). There was no significant difference in platform deviation, apex deviation, or axis deviation between the tilted implants and implants in the axial position ( P > 0.05). This analysis indicates that a dynamic navigation system can be used as a method of guidance to place intentionally tilted implants as accurately as axially positioned implants in the posterior maxilla, thereby preventing damage to the maxillary sinuses and the need to graft bone.